2006
DOI: 10.1002/jnr.21052
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl pyruvate attenuates kainic acid‐induced neuronal cell death in the mouse hippocampus

Abstract: Recent studies have shown that ethyl pyruvate (EP) acts as an anti-inflammatory molecule in several cell lines including RAW264.7 macrophages. However, the potential therapeutic value of EP for the treatment of the pathologic brain has not been investigated fully. In the present study, we examined whether EP has a beneficial effect on KA-induced neuronal cell death. Intracerebroventricular (i.c.v.) injection of 0.94 nmol (0.2 mug) of KA produced typical neuronal cell death in the CA1 and CA3 pyramidal layers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
41
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 31 publications
10
41
1
Order By: Relevance
“…While some of these studies support our finding that EP has no effect on ischemia, others maintain that EP has a neuroprotective effect in ischemia induced in the CNS (16,35,36). Cho et al (35) reported in a study on mice that EP reduced cell death in the hippocampus. In a study on rats, Moro and Sutton (36) reported a decrease in dead cell numbers in the hippocampus of animals in the group administered EP and that neuronal tissue loss also decreased in line with this.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…While some of these studies support our finding that EP has no effect on ischemia, others maintain that EP has a neuroprotective effect in ischemia induced in the CNS (16,35,36). Cho et al (35) reported in a study on mice that EP reduced cell death in the hippocampus. In a study on rats, Moro and Sutton (36) reported a decrease in dead cell numbers in the hippocampus of animals in the group administered EP and that neuronal tissue loss also decreased in line with this.…”
Section: Discussionsupporting
confidence: 79%
“…That study investigated pyramidal neuron deaths in the CA1 and CA3 regions of the hippocampus by the application of kainic acid by the intracerebroventricular route and by the administration of EP 12 h after the injection of kainic acid. At the end of the study, EP was seen to reduce cell deaths in the hippocampus (35). In a study on rats, Moro and Sutton (36) investigated the effects of sodium pyruvate (SP) and EP administered after head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Upon binding to non-NMDA glutamate receptors, KA provokes depolarization of neurons followed by severe status epilepticus, neurodegeneration, memory loss, neuronal cell death. [39][40] The possible role of NMDA and non-NMDA receptors in the regulation of neurotoxic responses (lethality, memory loss, hippocampal cell death, signal transduction systems), stimulated by KA was discussed by Lee et al 41 The neuronal degeneration after KA administration is generally accepted to be associated with a depletion of ATP and accumulation of [Ca 2þ ] i.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that khellin extracts have some antimicrobial activity; this might be attributable to both the khellin and visnagin constituents, which both seem to have antifungal, antibacterial, and antiviral activity [25]. In addition, several reports have demonstrated that drugs or compounds having an anti-inflammatory effect can show a neuroprotective effect [4,26,27]. Thus, we examined the effect of visnagin on proinflammatory mediators expression induced by KA.…”
Section: Discussionmentioning
confidence: 99%